2010
DOI: 10.1128/cvi.00389-09
|View full text |Cite
|
Sign up to set email alerts
|

Serum Bactericidal Antibody Response 1 Year after Meningococcal Polysaccharide Vaccination of Patients with Common Variable Immunodeficiency

Abstract: Some patients with common variable immunodeficiency (CVID) can generate an antibody response following vaccination with Neisseria meningitidis polysaccharide, but the duration of this protection is unknown. In this study, serum bactericidal antibody (SBA) responses to serogroup C N. meningitidis of 23 patients with CVID and 23 sex-and age-matched controls were measured 1 year after vaccination with the plain A/C meningococcal polysaccharide vaccine. The fold rise in serum bactericidal antibody geometric mean t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 31 publications
0
14
0
2
Order By: Relevance
“…Maturation of the immune system is suggested to be the most likely explanation of antibody sustainment [17] and the explanation of age dependant loss of protection. Additionally, some immune deficiency diseases and/or disorders have been reported in vaccine failure cases as additional risk factors [29,30]. Borrow et al studied the kinetics of antibody persistence and observed that antibody concentrations start to decline 1 month after the last dose and decrease exponentially as a function of time in infants [31].…”
Section: Discussionmentioning
confidence: 97%
“…Maturation of the immune system is suggested to be the most likely explanation of antibody sustainment [17] and the explanation of age dependant loss of protection. Additionally, some immune deficiency diseases and/or disorders have been reported in vaccine failure cases as additional risk factors [29,30]. Borrow et al studied the kinetics of antibody persistence and observed that antibody concentrations start to decline 1 month after the last dose and decrease exponentially as a function of time in infants [31].…”
Section: Discussionmentioning
confidence: 97%
“…In one study, 64% of CVID patients responded to the meningococcal vaccine [49]. Testing responses to other neoantigens such as the rabies virus may be logical, but there are currently few data in immunedeficient patients [50].…”
Section: Proposed Definition Of Common Variable Immune Deficiency (mentioning
confidence: 99%
“…Due to the severity of the disease we expected main diagnoses related to acute symptoms while meningococcal disease is confirmed. Additionally, relationship of meningococcal disease with concomitant infections [23][24][25] and immunodeficiency [26,27] has been described previously.…”
Section: Discussionmentioning
confidence: 99%